2002
DOI: 10.1097/00043426-200201000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion Volume in Infants With Very Low Birth Weight: A Randomized Trial of 10 Versus 20 mL/kg

Abstract: Transfusion with 20 mL/kg red blood cells produces a significantly greater increase in hemoglobin and hematocrit levels than does a transfusion with 10 mL/kg, without any detrimental effects on pulmonary function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 16 publications
2
26
0
Order By: Relevance
“…This amount agrees with actual studies about the administration of red blood cells. In doing so transfusion of 20 ml/kg produces no detrimental effects on pulmonary function [36] . Assuming an IGF-1-concentration of about 12 g/l in RBC, a transfusion volume of 15 ml/kg is equivalent to an application of 0.054 g IGF-1 for every kg bodyweight [(plasma !…”
Section: Discussionmentioning
confidence: 93%
“…This amount agrees with actual studies about the administration of red blood cells. In doing so transfusion of 20 ml/kg produces no detrimental effects on pulmonary function [36] . Assuming an IGF-1-concentration of about 12 g/l in RBC, a transfusion volume of 15 ml/kg is equivalent to an application of 0.054 g IGF-1 for every kg bodyweight [(plasma !…”
Section: Discussionmentioning
confidence: 93%
“…8 All svPRBCs were 20 cm 3 /kg and given over a period of 2 to 4 hours. 9 The determination of whether an infant needed a transfusion was based upon clinical reasons independent of this study protocol and usually within the suggested parameters. 7 Infant cytokine analysis occurred by obtaining 0.8 cm 3 of serum (1.6 cm 3 of whole blood) within 6 hours prior to the transfusion and 1-hour post completion of transfusion.…”
Section: Methodsmentioning
confidence: 99%
“…Frequency of blood transfusion in the low-birth-weight infants varies from 5 to as much as 10 per infant [2]. Blood transfusion practices seem to vary from one hospital to another and from one practitioner to another [1,3]. Volumes of blood required for transfusion are still issues of debate [3].…”
mentioning
confidence: 99%
“…Blood transfusion practices seem to vary from one hospital to another and from one practitioner to another [1,3]. Volumes of blood required for transfusion are still issues of debate [3]. Sometimes decisions to transfuse are based not on sound clinical judgment but on supposed needs.…”
mentioning
confidence: 99%